2019
DOI: 10.1111/jocn.15114
|View full text |Cite
|
Sign up to set email alerts
|

The experience of cancer‐related fatigue, exercise and exercise adherence among women breast cancer survivors: Insights from focus group interviews

Abstract: Aims and objectives To identify the experience of breast cancer survivors regarding cancer‐related fatigue, exercise and exercise adherence. Background Cancer‐related fatigue is a common symptom among cancer survivors that limits quality of life. Despite exercise being recommended as a viable solution to manage cancer‐related fatigue, relatively few research studies on the experience of cancer‐related fatigue and exercise adherence have been conducted. Design This was a qualitative study to identify breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(159 citation statements)
references
References 51 publications
3
154
2
Order By: Relevance
“…From the four focus group interviews [16], the 17 BCS were within 5 years of diagnosis, their age ranged from 20 to 69 years, and all had finished surgery and chemotherapy. At clinical stages 1-3, they had moderate or higher fatigue scores (four points or higher on a numerical rating scale of 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the four focus group interviews [16], the 17 BCS were within 5 years of diagnosis, their age ranged from 20 to 69 years, and all had finished surgery and chemotherapy. At clinical stages 1-3, they had moderate or higher fatigue scores (four points or higher on a numerical rating scale of 10).…”
Section: Resultsmentioning
confidence: 99%
“…For the focus group interviews, 17 BCS were convenience sampled to investigate the exercise experiences of BCS with moderate or greater fatigue. Using a semi-structured interview protocol, interviews took 1-2 h in each group, and recorded interviews were transcribed and analyzed [16].…”
Section: Methodsmentioning
confidence: 99%
“…In the field of lymphoedema treatment in female breast cancer survivors, there are several research works in which the benefits of exercise treatment in reducing lymphoedema have been collected [36][37][38][39]. In the studies of DiSipo et al [9] and Baumann et al [25] subjective improvements in the quality of life of the patients, anxiety (as occurs in other pathologies that alter the quality of life [40,41]), the decrease in lymphoedema (evaluated with volumetry) and, equally important, the non-appearance of adverse effects in the study population, are revealed.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Lack of knowledge about exercise and the experience of cancer-related fatigue were identified by individuals with cancer as obstacles to exercise in a recent Korean study. 13 A recent systematic review of the qualitative literature identified six studies of mixed quality reporting the experiences of women living beyond breast cancer participating in a supervised exercise intervention. 14 These studies all reported on group interventions, and the findings suggest that the group element may be beneficial.…”
Section: Introductionmentioning
confidence: 99%